Предмет: Алгебра,
автор: yumornoi3321
В2. Найдите значение выражения
(6а − 1)(6а + 1) − (12а − 5)(3а + 1)
при а = 0,2
И напишите как вы решали
Ответы
Автор ответа:
2
Ответ:
(6а-1)×(6а+1)-(12а-5)×(3а+1)= 6а^2+1^2-(12а-5)×(3а+1)=6а^2+1-(12а-5)×(3а+1), если а=0,2, то (6×0,2)^2+1-(12×0,2-5)×(3×0.2+1)=1.2^2+1-(2.4-5)×(0,6+1)=1,44+1-(-2,6)×1.6=2.44+2,6×1,6=2,44+4,16=6,6
Объяснение:
Вот;)
yumornoi3321:
Ответ должен быть 4,6
Похожие вопросы
Предмет: Математика,
автор: Natka1223
Предмет: Алгебра,
автор: Энза
Предмет: Математика,
автор: Flesh123
Предмет: Экономика,
автор: Tespy
Предмет: Литература,
автор: Аноним